2014
DOI: 10.1513/annalsats.201311-391fr
|View full text |Cite
|
Sign up to set email alerts
|

Electronic Cigarettes. Potential Harms and Benefits

Abstract: Use of electronic cigarettes, devices that deliver a nicotine-containing vapor, has increased rapidly across the country and globally. Perceived and marketed as a "healthier alternative" to conventional cigarettes, few data exist regarding the safety of these devices and their efficacy in harm reduction and treatment of tobacco dependence; even less is known about their overall impact on population health. This review highlights the recent data regarding electronic cigarette toxicity, impact on lung function, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
106
0
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 119 publications
(111 citation statements)
references
References 46 publications
0
106
0
3
Order By: Relevance
“…There are also two further cultural disruptors that have significant implications for both the maintenance of normative prohibition and for the normalisation proposition as previously developed. First is the explosion of the virtual market place of the internet as a source of drugs -hard to police and relatively easy to use (EMCDDA, 2015); and second, the new technology of e-cigarettes and techniques of vaping, the subject of heated debate as to whether this is normalising smoking and may serve as a gateway to use of other smokable drugs, or whether it is a public health breakthrough in assisting smoking cessation (Cressy, 2014;Drummond & Upson, 2014;Triggle, 2014). What is of interest for the normalisation debate is the smart advertising, design and market segmentation underpinning the new vaping market, creating a new clientele for a new, previously nonexistent product and means of using and inhaling a substance.…”
Section: Normalisation In a Contemporary Contextmentioning
confidence: 99%
“…There are also two further cultural disruptors that have significant implications for both the maintenance of normative prohibition and for the normalisation proposition as previously developed. First is the explosion of the virtual market place of the internet as a source of drugs -hard to police and relatively easy to use (EMCDDA, 2015); and second, the new technology of e-cigarettes and techniques of vaping, the subject of heated debate as to whether this is normalising smoking and may serve as a gateway to use of other smokable drugs, or whether it is a public health breakthrough in assisting smoking cessation (Cressy, 2014;Drummond & Upson, 2014;Triggle, 2014). What is of interest for the normalisation debate is the smart advertising, design and market segmentation underpinning the new vaping market, creating a new clientele for a new, previously nonexistent product and means of using and inhaling a substance.…”
Section: Normalisation In a Contemporary Contextmentioning
confidence: 99%
“…Discussion E-cigarettes are a controversial issue. Some experts suggested that e-cigarette use should be restricted or banned [19] because of their potential to increase tobacco cigarette consumption (reducing motivation to completely quit, acting as a gateway to smoking for non-smokers, or increasing smoking social acceptability) [19][20][21][22][23][24][25], and because concerns have been raised on the potential harms from propylene glycol [19,24], cartridge manufacturing and content quality (as refills may contain toxins and cause nicotine poisoning) [16,19,24], and on the potential risks from second-hand electronic smoking in indoor environments [15,19]. On the contrary, other experts claimed that e-cigarettes may be the centrepiece of a harm reduction strategy (being more attractive and cheap than other nicotine replacement therapies and facilitating smoking cessation, reduction or abstinence), that there is no evidence of undesirable uptake from non-smokers, that e-cigarettes pose only a small fraction of the risks of tobacco cigarettes (as tested liquids and aerosols contain negligible concentrations of toxicants and carcinogens, for e-cigarette users), n. of tobacco cigarettes smoked per day (or puffs per day for e-cigarette only smokers).…”
Section: Resultsmentioning
confidence: 99%
“…Although ECs appear to deliver lower levels of some chemicals compared with regular cigarettes, there is no evidence that they are a healthier alternative. 18 Drummond warned that the perception of ECs as a harm-reduction tool without adequate evidence can be likened to the promotion by tobacco companies of 'light' cigarettes, which were proven not to be safer. 18 …”
Section: Safety Of Ecsmentioning
confidence: 99%
“…18 Drummond warned that the perception of ECs as a harm-reduction tool without adequate evidence can be likened to the promotion by tobacco companies of 'light' cigarettes, which were proven not to be safer. 18 …”
Section: Safety Of Ecsmentioning
confidence: 99%